Using multiple self-sorting for switching functions in discrete multicomponent systems - Ghosh, Amit; Schmittel, Michael (Beilstein Journal of Organic Chemistry, 2020)
Over years self-sorting has developed into a powerful tool in supramolecular chemistry, for instance, to promote the error-free formation of intricate multicomponent assemblies. However, in order to use the enormous potential of self-sorting for sophisticated information processing more recent developments have focused on the reversible reconfiguration of multicomponent systems driven by multiple self-sorting protocols. The present mini review will provide an overview over the latest advancements in this field with a focus on reversibly switchable functions in discrete supramolecular systems.
Keywords: copper; fluorescence; self-assembly; self-sorting; zinc porphyrin